The School Effect. Beyond the Classroom - Javier Pascual Medina (Universidad Autónoma de Madrid, 2016)
The purpose of this investigation is to outline the importance of school components situated beyond the classroom, for instance, school managerial practices, resources, students vulnerability, level of autonomy, etc. Through quantitative analysis of secondary sources, a sample of 2882 Chilean vulnerable elementary schools was taken, all of which applied to Preferential School Grant (Subvención Escolar Preferencial, SEP), and have presented a diagnosis regarding institutional factors, and an improvement plan which were approved till September 2009. Moreover, their SIMCE results can be located on the government data bases. A multiple linear regression analysis was made in order to have a comparative look of the factors that influence learning outcomes on these schools. Results show that there is a strong relation between school managerial practices and students learning outcomes, influence that is much stronger than the one between this and teacher's abilities. It is also shown that the amount of resources that a school possess does not have a statistical significance when considered together with school managerial practices. These results could give us clues on how schools should use Preferential School Grant resources and on what public policies in Chile and Latin-America should focus on in order to enhance learning outcomes.